Potential of Legume Seeds from the Leguminosae Family as Material Source of Food and Medicine : A Literature Review - Dewi, Ni Made Ayu Gangga; Oktaviyanti, Nina Dewi; Sakulpanich, Aurapa; Kartini, Kartini (UI Scholars Hub, 2025)
Leguminosae, also known as Fabaceae, is the third largest plant family after Orchidaceae and Asteraceae. This review aimed to explore the potential of several legume species indigenous to Indonesia, from the Leguminosae family, as sources of food and medicine. The data used for the analysis were collected from various online databases such as PubMed, ScienceDirect, and Google Scholar. The results showed that there were 13 species of Leguminosae family plants found easily in Indonesia including Cajanus cajan, Canavalia ensiformis, Mucuna pruriens, Arachis hypogaea, Vigna subterranea, Glycine max, Phaseolus vulgaris, Phaseolus lunatus, Vigna radiata, Vigna unguiculata subsp. unguiculata, Vigna angularis, Vigna unguiculata subsp. sesquipedalis, and Pisum sativum. Among these species, several plants have been underutilized as food material, including C. cajan, C. ensiformis, M. pruriens, and P. lunatus. These 13 legume plants generally contain carbohydrates, proteins, starch, fats, and minerals, making them valuable as potential food sources. They also predominantly contain secondary metabolites, such as polyphenols and flavonoids (e.g., genistein, daidzein, cajanin), which have significant potential to be developed into pharmacologically active compounds.